MLIF Alleviates SH-SY5Y Neuroblastoma Injury Induced by Oxygen-Glucose Deprivation by Targeting Eukaryotic Translation Elongation Factor 1A2. - Qiuzhen Zhu (PLoS ONE, 2016)
Monocyte locomotion inhibitory factor (MLIF), a heat-stable pentapeptide, has been shown to exert potent anti-inflammatory effects in ischemic brain injury. In this study, we investigated the neuroprotective action of MLIF against oxygen-glucose deprivation (OGD)-induced injury in human neuroblastoma SH-SY5Y cells. MTT assay was used to assess cell viability, and flow cytometry assay and Hoechst staining were used to evaluate apoptosis. LDH assay was used to exam necrosis. The release of inflammatory cytokines was detected by ELISA. Levels of the apoptosis associated proteins were measured by western blot analysis. To identify the protein target of MLIF, pull-down assay and mass spectrometry were performed. We observed that MLIF enhanced cell survival and inhibited apoptosis and necrosis by inhibiting p-JNK, p53, c-caspase9 and c-caspase3 expression. In the microglia, OGD-induced secretion of inflammatory cytokines was markedly reduced in the presence of MLIF. Furthermore, we found that eukaryotic translation elongation factor 1A2 (eEF1A2) is a downstream target of MLIF. Knockdown eEF1A2 using short interfering RNA (siRNA) almost completely abrogated the anti-apoptotic effect of MLIF in SH-SY5Y cells subjected to OGD, with an associated decrease in cell survival and an increase in expression of p-JNK and p53. These results indicate that MLIF ameliorates OGD-induced SH-SY5Y neuroblastoma injury by inhibiting the p-JNK/p53 apoptotic signaling pathway via eEF1A2. Our findings suggest that eEF1A2 may be a new therapeutic target for ischemic brain injury.